LITERATURE REVIEW : EVALUASI PELAYANAN INFORMASI OBAT DI INSTALASI FARMASI - Ayu Werawati; Sayyidah Sayyidah; Gina Aulia; Fatwa Hikmatul Kurnia (Edu Masda Journal, 2022)
Quality is something that greatly affects customer satisfaction. Quality is the level of excellence of something, both goods and services. The level of consumersatisfaction can be measured from the comparison between consumer expectations with the reality felt by the consumer against an item or service. In health services, to be able to provide a quality health service, it must be started from the fulfillment of high ethical standards. Nowadays where there has been a shift in the orientation of pharmaceutical service management which prioritizes improving the quality of life of patients (patient oriented) rather than just selling drugs to patients (drug oriented), it is necessary for pharmacists to have an active role in carrying out their competencies so that drug use can be more optimal. It is also necessary to reduce drug-related problems. The lack of drug information provided can lead to a lack of patient understanding of the drug and can have a negative impact on the patient. The objective of this study was to identify the evaluation of drug information services against pharmaceutical service standards and drug information service guidelines. This research method is a literature review. The inclusion criteria used were Indonesian research with drug information services in pharmacy installations, articles published 2011-2021, full text articles. The result is that the evaluation of drug information services has met pharmaceutical service standards and meets drug information service guidelines.  ABSTRAKKualitas merupakan hal yang sangat mempengaruhi kepuasan konsumen. Kualitas merupakan tingkat keunggulan sesuatu, baik barang ataupun jasa, sehingga tingkat kepuasan konsumen dapat diukur dari perbandingan antara harapan dengan kenyatan yang didapat terhadap suatu barang atau jasa. Pada pelayanan kesehatan, untuk dapat memberikan suatu pelayanan kesehatan yang berkualitas harus dimulai dari pemenuhan standar etika yang tinggi. Di masa sekarang ini dimana telah terjadi pergeseran orientasi manajemen pelayanan kefarmasian yang mengutamakan peningkatan kualitas hidup pasien (patient oriented)  daripada sekedar memasarkan obat kepada pasien (drug oriented) menyebabkan perlunya peran aktif Apoteker untuk menjalankan kompetensi nya agar penggunaan obat dapat lebih optimal. Hal ini juga diperlukan untuk mengurangi masalah terkait obat. Kurangnya informasi obat yang diberikan dapat menyebabkan kurangnya pemahanan pasien akan obat dan dapat berdampak buruk pada pasien.  Penelitian ini bertujuan untuk mengidentifikasi evaluasi pelayanan informasi obat terhadap standar pelayanan kefarmasian dan pedoman  pelayanan informasi obat. Metode penelitian ini merupakan suatu Literature review. Kriteria inklusi yang digunakan adalah penelitian Indonesia dengan pelayanan informasi obat di instalasi farmasi, artikel diterbitkan 2011-2021, artikel full text. Hasil penelitian yang dihasilkan bahwa evaluasi pelayanan informasi obat  sudah memenuhi standar pelayanan kefarmasian dan  memenuhi pedoman  pelayanan informasi obat.